AN OVERVIEW OF THE RELATIONSHIP BETWEEN RESTORATIVE JUSTICE, SUSTAINABILITY, AND SHARED KNOWLEDGE PRODUCTION - Boin, Carla; Bairon, Sérgio (Seven Editora, 2026)
This article investigates the convergences and divergences between Restorative Justice and Sustainability, innovative paradigms for contemporary challenges, enhanced by mediation (Boin, 2019a) and Shared Knowledge Production (Bairon & Lazaneo, 2013). Restorative Justice, focused on repair and reconciliation through mediated dialogue (Zehr, 2002; Braithwaite, 2002), contrasts with Sustainability, which aims for intergenerational balance (WCED, 1987) and respect for planetary boundaries (Rockström et al., 2009). Both share repair, systemic vision, and community participation. Mediation, as a conflict facilitation tool (Boin, 2019a), and Shared Knowledge Production, co-creating knowledge (Bairon & Lazaneo, 2013), strengthen their integration in socio-environmental conflicts, education, and governance, especially from the perspective of environmental justice (Acselrad, 2009) and the epistemologies of the south (Santos, 2007). Despite resistances, cases like New Zealand and Indigenous productions offer ethical and practical solutions to global crises.DOI: https://doi.org/10.56238/sevened2026.008-009